Evaluation of Cenchrus purpureus varieties tolerant to drought in the western region of Cuba - Herrera, R. S. (Cuban Journal of Agricultural Science, 2022)
A three-year experiment was carried out to evaluate the agronomic performance of new varieties of Cenchrus purpureus (CT-600, CT-601, CT-602, CT-603, CT-605, CT-607, CT-608 and CT -609), tolerant to drought, obtained by in vitro tissue culture, and compared with its parent (CT-115) through a completely random design with five replications. There were significant differences between the height of the varieties and in both seasonal periods CT-605 stood out with values higher (P<0.05) at 90 cm. The leaves content (%) was only significantly different between the varieties in the dry season during the experimental stage, while the percentage of stems showed a similar response pattern. There were varieties that exceeded the DM yield of the control and especially the CT-605 with values of 21.82, 16.37 and 9.05 t DM/ha/year for the first, second and third year, respectively. With the exception of the first year, the varieties did not express their potential for biomass production under water stress conditions and future researches are suggested where rainfalls is less than 800 mm, as well as studying the effect of strategic fertilization on regimes of greater rainfall. Key words: water stress, tolerance, yields, population